Selfishness as a potential cause of crime: A prison experiment - Thorsten Chmura; Christoph Engel; Markus Englerth (Max Planck Institute for Research on Collective Goods, 2013)
For a rational choice theorist, the absence of crime is more difficult to explain than its presence. Arguably, the expected value of criminal sanctions, i.e. the product of severity times certainty, is often below the expected benefit. We rely on a standard theory from behavioral economics, inequity aversion, to offer an explanation. This theory could also explain how imperfect criminal sanctions deter crime. The critical component of the theory is aversion against outperforming others. To test this theory, we exploit that it posits inequity aversion to be a personality trait. We can therefore test it in a very simple standard game. Inequity averse individuals give a fraction of their endowment to another anonymous, unendowed participant. We have prisoners play this game, and compare results to findings from a meta-study of more than 100 dictator games with non-prisoners. Surprisingly, results do not differ, not even if we only compare with other dictator games among close-knit groups. To exclude social proximity as an explanation, we retest prisoners on a second dictator game where the recipient is a charity. Prisoners give more, not less.
Keywords: C93; D63; C91; A12; D03; K14; 330; Inequity aversion; crime; dictator game; selfishness; imperfect sanctions; social proximity; charity